KUALITASPELAYANANDI UNITPELAKSANA TEKNIS PERPUSTAKAAN UNIVERSITAS TANJUNGPURA PONTIANAK - Caturiani E.21109006 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Quality Service at the Tanjungpura University Library Technical Unit Pontianak, includes three aspects studied, including: (a). Attitudes and behavior of workers in providing services. (b). Factors inhibiting the Library in providing good service to service users. (c). Efforts made the Library in improving the quality of service to service users. This study uses the analytical descriptive method with the qualitative technique in the data processing. As for theinformantsin this study weretheparties involvedin the service andthosewhoreceivethose serviceswithin the scope ofthe Tanjungpura University Library Pontianak.The research found that the attitudes and behavior of workers in providing services is a courtesy and on time. While the officers were the limiting factor in providing services to service users, including: (a). The lack of computer tools that contribute to hamper the smooth services in the circulation room, and (b). Network or system to access services for borrowing, repayment, and an extension of the book on line using the application senayan often jammed or error so that the transaction can not run smoothly. The efforts that have been carried out by the Library in improving the quality of care is to provide direction guidance relating to the use of computer-related skills with borrowing, repayment, and an extension of the book for faster, timely and thorough in providing services to service users. In addition, the Library has also sought to improve the quality of services to service users, among others, by providing information about borrowing, repayment, and an extension of the book procedures, and the provision of facilities and infrastructure. Keywords:Quality of Service, Behavioral Services Officer, Obstacles of Srvices Quality, and Effort Service Officers.